Measuring the effectiveness of transportation applications among SAL students in UMK Pengkalan Chepa - Ahmad Wafiudeen Rosidi; Raveen Kumar M.Murailee; Aliyana Najwa Mustapha @ A.Rahman; Cheng Ee Khin (2024)
Transportation application services are experiencing a growing popularity in Malaysia. Transportation applications have significantly enhanced the convenience and advantages for students by facilitating their everyday travel to various destinations. The aim of this study is to assess the satisfaction of SAL students at UMK Pengkalan Chepa with transport applications, analyse the connection between payment security and the effectiveness of these applications, evaluate the impact of accessibility on their effectiveness, and identify the relationship between time accuracy and their effectiveness. The scope of this study aligns with the research question and research aims. This study utilized a quantitative technique to determine the entire population of SAL students at UMK Pengkalan Chepa, which was found to be around 783 students. Therefore, a sample size of 260 respondents was necessary to complete the questionnaire. The researcher utilized the Google Form platform to administer the questionnaire and employed the WhatsApp application as a communication medium with the responders. The study employed quantitative research methods. The data was analyzed using SPSS software, employing descriptive analysis, reliability testing, Pearson correlation coefficient, and hypothesis testing. This study highlights the significant significance of addressing customer satisfaction, payment security, accessibility, and timeliness in transportation applications to enhance overall effectiveness. It emphasizes the need for customized improvements that align with the specific requirements of SAL students at UMK Pengkalan Chepa, aiming for a more gratifying and efficient transportation experience. The study suggests that future research should address the constraints, such as the limited sample size, by including a larger student population. Additionally, the study proposes enhancing the practical applications of the findings. The results emphasize the importance of customizing enhancements to address the unique requirements of students, so guaranteeing a more gratifying and streamlined transit experience. The recommendations encompass increasing the diversity of the student population, improving the implementation of practical skills, and optimizing the integration of university systems. This study presents the findings and evaluates the feasibility of achieving the study's objectives. This research includes references to enhance the investigation of elements that impact the efficacy of transport applications among students.